Degradabilitas bahan organik dan produksi total Vollatile Fatty Acids (VFA) daun kelor (Moringa oleifera) dalam rumen secara in vitro (Faculty of Animal Science, Universitas Brawijaya, 2017)
The research was aimed to examine nutritive potency of Moringa oleifera and Leucaena leucocephala leaves according to ruminal organic matter degradability and total volatille fatty acids production in vitro. The ruminal degradability of organic matter was determined after 1, 2, 4, 8, 12, 24 and 48 of single batch culture incubation. The data weretested using T test. The result showed that degradable and potential degradable fractions of M. oleifera leaf organic matter werehigher (p <0.05) than that of L. Leucocephala leaf organic matter Production of rumen total VFA from M. Oleifera leaf higher (P<0.05) than from L. leucocephala leaf. The nutritive potency of M. oleifera leaf was better than L. Leucocephala.